New orchids in the flora of Vietnam Ⅴ (Orchidaceae, Aeridinae) - Averyanov, Leonid V.; Thai, Tran Huy; Nguyen, van Canh; Truong, Ba Vuong; Maisak, Tatiana V.; Doan, Nga Thi; Nguyen, Khang Sinh (Phytotaxa, 2022)
This paper presents new data on the orchid diversity of Vietnam obtained in 2020–2022. It comprises descriptions of two species new for science (Cleisostoma tatonii and Sarcoglyphis hiepii) and descriptions of four species new for the flora of Vietnam (Cleisostoma aspersum, Gastrochilus nanus, Micropera mannii and Trichoglottis ramosa). All species found for the first time in Vietnam are morphologically slightly different from the individuals in their main distribution area. Data on accepted names, main synonyms, etymology (for newly described species), morphological description, studied specimens, ecology, phenology and distribution, conservation status assessment, brief taxonomic notes, and illustrations are provided for each species listed.